2018
DOI: 10.1016/j.nefro.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia del síndrome complejo de malnutrición e inflamación y su correlación con las hormonas tiroideas en pacientes en hemodiálisis crónica

Abstract: Low T3 and FT3 levels are correlated with malnutrition and inflammation parameters. Malnutrition-inflammation complex syndrome can affect serum concentrations of thyroid hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As a consequence to the convergent input of inflammation in the pathophysiology of PEW and CV disease, the term malnutrition-inflammation-atherosclerosis syndrome was established in patients with ESKD [64]. Remarkably, a prevalence of MIA of 53.9% is reported in patients on HD [65]. Consistent with CV impairments being the cornerstone of MIA, the finding that PEW (by MNA and CRP) associates with impairments in cardiorespiratory function, assessed via the 6MWT, is not unexpected.…”
Section: Plos Onementioning
confidence: 92%
“…As a consequence to the convergent input of inflammation in the pathophysiology of PEW and CV disease, the term malnutrition-inflammation-atherosclerosis syndrome was established in patients with ESKD [64]. Remarkably, a prevalence of MIA of 53.9% is reported in patients on HD [65]. Consistent with CV impairments being the cornerstone of MIA, the finding that PEW (by MNA and CRP) associates with impairments in cardiorespiratory function, assessed via the 6MWT, is not unexpected.…”
Section: Plos Onementioning
confidence: 92%
“…These findings of higher FT3 and T4 in farmers are in line with the work of Kongtip (2019), which reported an increase in TSH, FT3, T3, and T4 levels in conventional farmers relative to organic farmers in Thailand [ 6 , 7 ]. The higher frequency of hypothyroid for FT3 in non-farmers should be further explored, because a study by Chavez (2013) showed that 11.7% of respondents with complex inflammatory malnutrition syndrome had a low FT3 level, and this was also associated with IL-6, C-reactive protein, and albumin [ 29 ]. Low FT3 is included in non-thyroid disease (NTI), which is a counter-regulatory response that causes a waste of energy and protein in acute and chronic stress conditions, such as uncontrolled diabetes mellitus with ketoacidosis, myocardial infarction, and severe myocardial ischemia, and in almost all severe diseases [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have widely investigated the prognostic value of the presence of non-thyroidal illness for long-term mortality in chronic HD patients and its potential association with low-grade inflammation, a common feature of uraemia [ 34 ]. In haemodialysed patients, serum T3 and fT3 levels have been inversely correlated with malnutrition and inflammation parameters (hsCRP, interleukin-6), because malnutrition–inflammation complex syndrome can affect serum concentrations of thyroid hormones [ 9 , 10 , 31 , 35 ]. On the contrary, previous studies reported an association between a state of malnutrition–inflammation–atherosclerosis syndrome and poor dialysis outcome in ESRD patients [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%